Effects of learning, networking and innovation adoption on successful entrepreneurs in Central Java, Indonesia - Setyawati, Sri Murni; Mohd Shariff, Mohd Noor; Saud, Mohammad Basir (Centre for Promoting Ideas, 2011)
This paper aims to test models of learning, networking, and innovation adoption on successful entrepreneurs in Central Java, Indonesia. The study was dependent on a survey conducted on 580 subjects using a random sampling technique. Structural Equation Model (SEM) was used to analyse the data. The results showed that learning and networking have a significant effect on innovation adoption. Consequently, innovation adoption significantly affects the success of the entrepreneurs.Based on the findings, implications to practice are offered.